2021
DOI: 10.1155/2021/9087094
|View full text |Cite|
|
Sign up to set email alerts
|

Research on Enterprise Employee Performance Appraisal Management System Based on CS Architecture

Abstract: Aiming at the problems of poor system throughput and poor performance appraisal indicators in traditional enterprise employee performance appraisal management systems, a corporate employee performance appraisal management system based on the CS architecture was designed. Firstly, the system architecture of performance appraisal system is built, the system logical architecture design is determined, and the functional modules of the appraisal management system are analyzed. Then, the influencing factors of emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…According to [1], the essence of evaluating employees' performance in any tertiary institution is to realize the goals of the institution by measuring the contribution of each employee. It is of great significance to consider the development of performance appraisal as an important work agenda of enterprises and take it as an important part of management [2]. However, the most important single purpose served by performance appraisals is to let employees know where they stand.…”
Section: Review Existing Literaturementioning
confidence: 99%
“…According to [1], the essence of evaluating employees' performance in any tertiary institution is to realize the goals of the institution by measuring the contribution of each employee. It is of great significance to consider the development of performance appraisal as an important work agenda of enterprises and take it as an important part of management [2]. However, the most important single purpose served by performance appraisals is to let employees know where they stand.…”
Section: Review Existing Literaturementioning
confidence: 99%
“…This study combines the in-depth learning model with experimental analysis based on the cross-border e-commerce firms' performance lag calculation and analysis. • Lin [23] have suggested that a corporate system was established based on the CS design in order to address the issues with low system throughput and inadequate performance appraisal indicators in traditional enterprise staff performance appraisal management systems'. The functional elements of the evaluation management system were examined and the system architecture for the performance appraisal system was first constructed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The outcome is a matrix that describes the model's performance for every class. Equation so establishes it equation (23),…”
Section: ) Accuracymentioning
confidence: 99%
“…This provides a theoretical basis for effectively evaluating and managing enterprise tacit knowledge, which is essential for evaluating IT systems. In addition to these references, other relevant topics include performance appraisal (Lin, 2021;Peng, 2022), sustainability (Dergachova et al, 2019;Zhang et al, 2021), and low carbon development (Zhao et al, 2015). These topics provide insights into evaluating the performance and impact of IT systems in relation to employee performance, sustainability goals, and environmental considerations.…”
Section: Inten�on To Use Usementioning
confidence: 99%